Towards accessibility in educational games: a framework for the design team - Cezarotto, Matheus Araujo; Chamberlin, Barbara (InfoDesign, 2021)
Information design is relevant to game design: especially the design of educational games which must include best practices of game development and the delivery of information to the player. Games and players interact in important ways: the game communicates with the player on how to start and play the game, the player decides what to do in the game, and the player must communicate effectively with the game through different actions. Without attention to accessibility, the game may cause some players informational and interactional barriers. This study discusses accessibility in educational games, including communication channels, users' cognitive processes, and informational inputs. A framework offers a way for developers to think through design which reflects different needs related to accessibility. With this framework, designers can create games that address four key areas of need (vision, hearing, motor control, and cognitive); recognize how game interactions are impacted by those needs; and acknowledge that all players fall somewhere on a spectrum of need within each of those areas.